Black Phosphorus/Polymers: Status and Challenges. Issue 37 (29th July 2021) - Zhang, Ye; Ma, Chunyang; Xie, Jianlei; Ågren, Hans; Zhang, Han
Abstract: As a newly emerged mono‐elemental nanomaterial, black phosphorus (BP) has been widely investigated for its fascinating physical properties, including layer‐dependent tunable band gap (0.3–1.5 eV), high ON/OFF ratio (10 4 ), high carrier mobility (10 3 cm 2 V −1 s −1 ), excellent mechanical resistance, as well as special in‐plane anisotropic optical, thermal, and vibrational characteristics. However, the instability caused by chemical degradation of its surface has posed a severe challenge for its further applications. A focused BP/polymer strategy has more recently been developed and implemented to hurdle this issue, so at present BP/polymers have been developed that exhibit enhanced stability, as well as outstanding optical, thermal, mechanical, and electrical properties. This has promoted researchers to further explore the potential applications of black phosphorous. In this review, the preparation processes and the key properties of BP/polymers are reviewed, followed by a detailed account of their diversified applications, including areas like optoelectronics, bio‐medicine, and energy storage. Finally, in accordance with the current progress, the prospective challenges and future directions are highlighted and discussed. Abstract : Recent progress in black phosphorus/polymer (BP/polymers) research is highlighted, including the preparation methods, a comprehensive introduction of their prop erties, and a detailed account of their applications in optoelectronics, biomedicine, energy‐storage devices, flame retardancy, and information storage. Forward‐looking perspectives on the current challenges are also provided.